Teachers ' Feedback Provision Practices: A Case of Geography Subject Continuous Assessment Activities in Tanzanian Secondary Schools - Yotham, Tawi; Ndabi, Joyce (Papers in Education and Development, 2024)
This study examined secondary school teachers ' feedback provision practices in Geography continuous assessment activities in Tanzania. It used a concurrent mixed methods approach to collect data through interviews, focus group discussions, questionnaires, and documentary reviews. The study comprised 418 respondents, including heads of schools, Form Three geography teachers, and Form Three students who were purposely and randomly chosen. The descriptive data demonstrate that teachers do not deliver effective feedback because their feedback lacks clarity, descriptiveness, specificity, and continuity. The study concludes that the feedback provided by geography teachers is ineffective. The findings highlight the imperative for the continuing professional development programmes to enhance teacher ' s knowledge and skills essential for delivering effective feedback in schools. Keywords: Feedback, effective feedback, geography learning, geography assessment, continuous assessment